Superelement Verification in Complex Structural Models - B. Dupont; E. Pillet; S. Cogan (Shock and Vibration)
The objective of this article is to propose decision indicators to guide the analyst in the optimal definition of an ensemble of superelements in a complex structural assembly. These indicators are constructed based on comparisons between the unreduced physical model and the approximate solution provided by a nominally reduced superelement model. First, the low contribution substructure slave modes are filtered. Then, the minimum dynamical residual expansion is used to localize the superelements which are the most responsible for the response prediction errors. Moreover, it is shown that static residual vectors, which are a natural result of these calculations, can be included to represent the contribution of important truncated slave modes and consequently correct the deficient superelements. The proposed methodology is illustrated on a subassembly of an aeroengine model.